ADOPTION AND ANNEXATION BETWEEN SHARIA AND IRAQI LAW (American Journal of Research in Humanities and Social Sciences, 2023)
This paper aims to clarify the traditional or common social aspects known in ancient Arab societies, especially Iraqi society, which are in contact with what the necessities of individual interests of those societies require, as well as what the necessities of the groups in them require, and how they influence the formation, development, and growth of those groups and the building of their beliefs, values, and principles. Discussing the role of these social manifestations in their relationship with the basic needs of society, especially their role in forming the family, which is the basic building block for the formation of society.